2012
DOI: 10.5897/ajb12.1275
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and computational analysis of a water stress inducible copper-containing amine oxidase gene (CuAO) from tea plant [Camellia sinensis (L.) O. Kuntze]

Abstract: Copper-containing amine oxidase (CuAO) is the enzyme known to play diversity of function in plant responses to environmental stresses through its reaction products. Here, for the first time we report full length cDNA encoding CuAO protein from a drought tolerant tea cultivar. It was found to be 785 bp long with a 70 bp 5ʹ-UTR, 193 bp 3ʹ-UTR, 522 bp mORF and a polyA adenylational signal. It codes for a polypeptide of 173 amino acids having predicted molecular weight and isoelectric point of 19 KDa and 7.75 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The copper-containing amine oxidase (CuAO) is a kind of amine oxidase with various physiological functions, which is involved in plant cell differentiation and response to abiotic stress. Bharalee et al. (2012) found that the induced CuAO gene expression was significantly higher than that of the control under drought conditions, which could improve the resistance of tea to abiotic stress and prevent the accumulation of reactive oxygen species caused by drought.…”
Section: Discussionmentioning
confidence: 93%
“…The copper-containing amine oxidase (CuAO) is a kind of amine oxidase with various physiological functions, which is involved in plant cell differentiation and response to abiotic stress. Bharalee et al. (2012) found that the induced CuAO gene expression was significantly higher than that of the control under drought conditions, which could improve the resistance of tea to abiotic stress and prevent the accumulation of reactive oxygen species caused by drought.…”
Section: Discussionmentioning
confidence: 93%